A study of steady-state thermal distribution on circular plate using ANSYS - Akop, Mohd Zaid; Jikol, Favian; Salim, Mohd Azli; Mohamed Arifin, Yusmady (Universiti Malaysia Perlis, 2021)
The purpose of this study is to investigate the thermal behavior of a circular-shaped hot plate when certain thermal load is applied. The hot plate is a part of hot surface deposition test equipment, and is placed on top of a heater block. The temperature distribution on the hot plate will indicate the highest temperature, and whether the temperature generated is as per required in the hot surface deposition test. Modelling of the heater block and the steady-state thermal analysis is conducted experimentally using ANSYS Release 16.2 software. The maximum temperature of the hot plate is compared to the applied temperature on the heater block. It is shown that there is dissimilarity of temperature between the hottest spot on the hot plate surface and the temperature applied. When conducting the real deposition test, the exact required temperature of the hot plate can be obtained by altering the temperature setting and measured accurately by using thermometer